ANALISIS PEMBERLAKUAN PSBB TERHADAP NILAI TUKAR RUPIAH DAN STOCK RETURN (Studi Kasus Pandemi Covid-19 Tahun 2020) - Rahmania Fitriani; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2021)
The purpose of this study is to analyze whether there are differences in the rupiah exchange rate and stock returns in the implementation of large-scale social restrictions (PSBB) during the 2020 Covid-19 pandemic. The sample in this study uses a purposive sampling technique. The research data obtained a sample of 194 manufacturing companies. The analytical method of this research is the Descriptive Statistical Test, Normality Test, and Hypothesis Testing. The results showed that there was a difference in the exchange rate before and after the implementation of the PSBB and there was a difference in stock returns before and after the implementation of the PSBB. Keywords : PSBB enforcement, Rupiah Exchange Rate, and Stock Return